Социально-экономические предпосылки возникновения и развития кооперации на Кубани в конце ХІХ – начале ХХ вв. - Сидоренко, Т.Н. (Історичний архів. Наукові студії, 2014)
Рассмотрено причины возникновения и развития кооперации на Кубани.
Предпосылки для кооперирования населения области стали складываться в конце ХIХ в.
в связи с быстрым развитием аграрного капитализма, чему способствовал массовый
переселенческий поток. В связи с активной миграцией населения и выгодным
географическим положением процесс социально-экономического развития, а так же
кооперирования на Кубани в начале ХХ в. шел более интенсивно, чем в других регионах
страны. Рассмотрены причины бурного развития кредитных кооперативов и их вклад
в развитие аграрного сектора экономики области. Розглянуто причини виникнення і розвитку кооперації на Кубані. Передумови для
кооперування населення області стали складатися наприкінці ХIХ ст. у зв’язку з
швидким розвитком аграрного капіталізму, чому сприяв масовий переселенський потік.
У зв’язку з активною міграцією населення і вигідним географічним положенням процес
соціально-економічного розвитку, а так само кооперування на Кубані на початку ХХ ст.
йшов інтенсивніше, ніж в інших регіонах країни. Розглянуто причини бурхливого
розвитку кредитних кооперативів та їх внесок у розвиток аграрного сектора
економіки області. Summary This article discusses the reasons and prerequisites of emergence and
development of cooperative movement in Kuban at the end of XIX – the beginning of the
XX century. It is noted that the socio-economic conditions for the emergence of cooperatives in
Russia began to form in the post-reform era when rapidly began to develop commodity-money
relations. In these conditions cooperation was one of ways by which small producers and
consumers were involved in system of the market capitalist relations, and at the same time –
one of forms of protection of their interests from any operation of intermediaries – dealers,
dealers, and also from large businessmen.
In the Kuban region the prerequisite for cooperation of the population began to develop at
the end of the XIX century in connection with fast development of capitalism mainly in agrarian
sector of economy that was promoted by a mass resettlement stream. Due to the active
migration of the population at the beginning of the XX century and an advantageous
geographical position process of social and economic development and as cooperation in
Kuban went more intensively, than in other regions of the country. Important factor of powerful
development of cooperation of Kuban were weakness of serf remnants and insignificant percent
of large landowner manors. Development of the commodity-money relations in agriculture of
Kuban had that feature that it occurred mainly because of small Cossack and peasant land use
and small owners were most interested in cooperation.
Especially rapidly at the beginning of the century in the Kuban region developed credit
cooperatives in the form of credit and loan-and-savings associations. The article discusses the
reasons of the rapid development of credit cooperatives and their contribution to the
development of agrarian sector of economy of the region. The main activities of other forms of
the cooperative organizations in Kuban are shown. It is specified that cooperation was the most
important factor of development of economy of the region at the beginning of the XX century.